2022
DOI: 10.1093/bioinformatics/btac495
|View full text |Cite
|
Sign up to set email alerts
|

Detecting DNA of novel fungal pathogens using ResNets and a curated fungi-hosts data collection

Abstract: Background Emerging pathogens are a growing threat, but large data collections and approaches for predicting the risk associated with novel agents are limited to bacteria and viruses. Pathogenic fungi, which also pose a constant threat to public health, remain understudied. Relevant data remain comparatively scarce and scattered among many different sources, hindering the development of sequencing-based detection workflows for novel fungal pathogens. No prediction method working for agents ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 118 publications
(175 reference statements)
1
11
0
Order By: Relevance
“…Figure 8 shows the screenshot image of develop dynamic web server. We found 2 most closely related works [18][19] in the direction of bacterial classification using WGS data similar to our work, hence we selected these for comparison with the proposed work.…”
Section: Web Server For Deployment Of Proposed Ai Modelsupporting
confidence: 54%
See 3 more Smart Citations
“…Figure 8 shows the screenshot image of develop dynamic web server. We found 2 most closely related works [18][19] in the direction of bacterial classification using WGS data similar to our work, hence we selected these for comparison with the proposed work.…”
Section: Web Server For Deployment Of Proposed Ai Modelsupporting
confidence: 54%
“…With our work, we are reporting the performance of model over a huge test data of more than 12,000 whole genome sequences, whereas models trained over more than 8000 whole genome sequences, i.e., total size of the data is more than 20,000 SRA whole genome sequences. Moreover, we have made our model up on a dynamic web server so that it can be tested or challenged with respect to its performance quoted anytime by anyone, which is missing in these works [18][19]. Our web server is blind-tested over any type of sequences by a few volunteers, and we reported that performance too.…”
Section: Web Server For Deployment Of Proposed Ai Modelmentioning
confidence: 91%
See 2 more Smart Citations
“…We propose to augment our system as the next step of a sequencer generating raw sequences to classify them into ESKAPEE pathogens in realtime as a modern diagnostic solution. As we trained our models over SRA data produced by a variety of sequencing devices, it is not dependent or biased for a specific sequencer as reported in earlier works [18][19]. The major upheaval from the existing systems is that it takes the bacterial classification process from wet lab to entirely in-silico labs.…”
Section: Introductionmentioning
confidence: 99%